TOURISM IN FUNCTION OF DEVELOPMENT OF THE REPUBLIC OF SERBIA - ?ourism in the Era of Digital Transformation - Senić, Vladimir (Hotel and Tourism Management, 2018)
-Conclusions of the Third International Scientific Conference held at the Faculty of Hotel Management and Tourism in Vrnja?ka Banja, May 31 – June 2, 2018